PEMANFAATAN MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW UNTUK MENINGKATKAN PEMAHAMAN MAHASISWA S1 PGSD UNIROW TENTANG MODEL-MODEL PEMBELAJARAN TERPADU PADA MATA KULIAH PEMBELAJARAN TEMATIS - Wiratsiwi, Wendri (Universitas Nahdatul Ulama Surabaya, 2017)
The purpose of this research to improve understanding of learning for fourth students at Unirow primary teacher education in 2015/2016 academic year abaut integrated learning models of Thematic subject learning use Jigsaw cooperative models. The methode of research is classroom action research. The results of this research show that using jigsaw cooperative models on integrated learning models can improve understanding of learning to PGSD Unirow fourth students at Unirow primary teacher education in 2015/2016 academic year in Thematic Learning. This is reflected in some indicators 1) Student activity during use jigsaw cooperative models achieve success with success percentage 66.11% in the first cycle and 90.93% in the second cycle; 2) the activity of lecturers during the use jigsaw cooperative models achieve success with success percentage 68.45% in the first cycle and 95.24% in the second cycle; 3) classical completeness achieve success with success percentage 75% in the first cycle to 86.11% in the second cycle. It can be concluded that the jigsaw cooperative model can improve understanding of learning student for fourth students at Unirow primary teacher education in 2015/2016 academic year abaut integrated learning models of Thematic subject learning.Jigsaw cooperative models